Ceriantharia (Cnidaria) from Australia, New Zealand and Antarctica with descriptions of four new species - Stampar, Sérgio N. [UNESP]; Mills, V. Sadie; Keable, Stephen J. (Australian Museum, 2020)
The fauna of Ceriantharia (tube-anemones) in the South Pacific is poorly studied with only four shallow-water species formally described and these animals are known from few regions in very specific reports. Cerianthids are organisms that live in a tube constructed with a special type of cnidae and are currently grouped in an exclusive subclass of Anthozoa. This study addresses specimens from three natural history collections, the Australian Museum and the Museum and Art Gallery of the Northern Territory (both Australia), and the National Institute of Water & Atmospheric Research (NIWA) Invertebrate Collection (New Zealand), focusing on specimens from the Coral Sea, Tasman Sea and Antarctic Ocean. As a result, four new species are described and one synonymized. This highlights the ongoing need for taxonomic studies in the region, especially for marine organisms. Also, in this study, we offer tables with morphological characters that can be useful for species identification in each genus. Copyright:
Keywords: Deep sea; Marine invertebrates; South Pacific; Taxonomy